Managing the Maze: Advanced Approaches to Pediatric Cataract Complications - Imelda, Eva; Jannah, Siti Rain; Adev, Sarra Mutiara; Toshniwal, Nikhil (Graha Primera Saintifika, 2025)
Complicated cataract is a condition characterized by opacification of the crystalline lens due to intraocular diseases, particularly inflammatory conditions and other abnormalities. It often affects younger age groups, leading to visual impairment that typically requires surgical intervention. A 3-year-old girl presented with complaints of white spots in both eyes for one week. Following a physical examination and ultrasonography, she was diagnosed with bilateral complicated cataracts. The patient was scheduled for procedures including synechiolysis and irrigation-aspiration. However, due to intraoperative complications, additional procedures were necessary. Postoperatively, the patient was treated with antibiotic and anti-inflammatory medications and underwent optical rehabilitation using spectacles. This case highlights the management of pediatric cataracts and the challenges involved, with particular focus on postoperative optical rehabilitation to prevent amblyopia. Prompt and appropriate treatment of cataracts in children is crucial to clear the visual axis and restore a clear retinal image, thereby preventing the development of amblyopia.